Larvicidal activity of Syzygium aromaticum (L.) Merr and Citrus sinensis (L.) Osbeck essential oils and their antagonistic effects with temephos in resistant populations of Aedes aegypti - Oliveira Araujo, Adriana Faraco de [UNESP]; Ribeiro-Paes, Joao Tadeu [UNESP]; Deus, Juliana Telles de; Holanda Cavalcanti, Sorates Cabral de; Nunes, Rogeria de Souza; Alves, Pericles Barreto; Graca Macoris, Maria de Lourdes da (Fundaco Oswaldo Cruz, 2016)
Environmentally friendly botanical larvicides are commonly considered as an alternative to synthetic larvicides against Aedes aegypti Linn. In addition, mosquito resistance to currently used larvicides has motivated research to find new compounds acting via different mechanisms of action, with the goal of controlling the spread of mosquitos. Essential oils have been widely studied for this purpose. This work aims to evaluate the larvicidal potential of Syzygium aromaticum and Citrus sinensis essential oils, either alone or in combination with temephos, on Ae. aegypti populations having different levels of organophosphate resistance. The 50% lethal concentration (LC50) of the essential oils alone and in combination with temephos and the influence of essential oils on vector oviposition were evaluated. The results revealed that essential oils exhibited similar larvicidal activity in resistant populations and susceptible populations. However, S. aromaticum and C. sinensis essential oils in combination with temephos did not decrease resistance profiles. The presence of the evaluated essential oils in oviposition sites significantly decreased the number of eggs compared to sites with tap water. Therefore, the evaluated essential oils are suitable for use in mosquito resistance management, whereas their combinations with temephos are not recommended. Additionally, repellency should be considered during formulation development to avoid mosquito deterrence.
Keywords: Syzygium aromaticum; Citrus sinensis; Aedes aegypti; vector control; larvicide; dengue